EXPLORE BUSINESS OPPORTUNITYS IN THE SPORT INDUSTRY IN BEKASI: WEB-BASED FUTSAL FIELD RENT INFORMATION SYSTEM - Ferry Kurniawan; Achmad Fauzi; Ahmad Muchlisin Natas Pasaribu; Rizty Dwi Nurazizah; Alfath Nare Utama; Aditya Tri Syahbanu; Ade Ilham Prasetyo; Andhika Rifki Prasetyo; Bagus Naufal Putra Shawa (Draf Solusi Indonesia, 2023)
The nation's economic development and the sports sector both depend on the sports industry. Offers field rental for sports, especially futsal. Companies that rent out futsal courts are called